Spectral characteristics of boundary layer turbulence over irregular terrain - Eversole, Rae Ann, author; Department of Atmospheric Science, Colorado State University, publisher (Colorado State University. Libraries, 1979)
The spectral behavior of turbulence in a convectively unstable boundary layer over undulating terrain is discussed. The wind and temperature fluctuations were measured with fast response sensors mounted on the 300 m tower at the Boulder Atmospheric Observatory (BAO). The boundary layer is divided into three layers (surface, matching, and mixed). The spectra of each layer are normalized using the appropriate scaling rules. The generalized spectra follow similarity theory. This paper compares the BAO results with the data obtained during AFCRL's field experiments in Kansas (1968) and Minnesota (1973) over flat, uniform terrain. The spectra in the inertial subrange decrease in the surface layer and become constant in the mixed layer. The ratio of the spectral intensities between the transverse and longitudinal velocity components is 4/3, the -5/3 power law exists, and the cospectra vanish in the inertial subrange; consequently, local isotropy is observed. The wavelength corresponding to the logarithmic spectral peak is greater over rolling terrain than flat terrain for all the spectra in the surface, matching, and mixed layers. Both the horizontal and vertical velocity components exhibited larger length scales in the mixed layer than 1.5zi as observed at Minnesota. At BAO, the fluctuating temperature and vertical velocity component energy containing eddies were of comparable size. Since this was not observed over flat terrain, the irregular terrain may be a contributing factor to the observed differences. The dissipation rates of turbulent kinetic energy are examined in the surface and mixed layers. In the surface layer BAO dissipation rates agree well with those calculated in Minnesota, but increased more rapidly than the Kansas dissipation rates. In the mixed layer, however, the dissipation rate of turbulent kinetic energy is high at BAO and Minnesota for unknown reasons. In addition, the normalized standard deviation of vertical velocity and temperature are compared with the Kansas results and found to agree well.
June 1979.
Keywords: Boundary layer (Meteorology); Turbulence